109 Assessing the number of fire fatalities in a defined population. (1st September 2016) - Jonsson, Anders; Bergqvist, Anders; Andersson, Ragnar
Abstract : Background: Fire-related fatalities and injuries have become a growing governmental concern in Sweden, and a national vision zero strategy has been adopted stating that nobody should get killed or seriously injured from fires. There is considerable uncertainty, however, regarding the numbers of both deaths and injuries due to fires. Different national sources present different numbers, even on deaths, which obstructs reliable surveillance of the problem over time. We assume the situation is similar in other countries. This study seeks to assess the true number of fire-related deaths in Sweden by combining sources, and to verify the coverage of each individual source. By doing so, we also wish to demonstrate the possibilities of improved surveillance practices. Methods: Data from three national sources were collected and matched; a special database on fatal fires held by The Swedish Contingencies Agency (nationally responsible for fire prevention), a database on forensic medical examinations held by the National Board of Forensic Medicine and the cause of death register held by the Swedish National Board of Health and Welfare. Results: The results disclose considerable underreporting in the single sources. The national database on fatal fires, serving as the principal source for policymaking on fire-prevention matters, underestimates the true situation by 20%. Its coverage of residential fires appears to be better than other fires. Conclusions: Systematic safety work and informed policy-making presuppose access to correct and reliable numbers. By combining several different sources, as suggested in this study, the national database on fatal fires is now considerably improved and includes regular matching with complementary sources.